(untitled) (Journal of history, 2023)
The article considers the concept and practical experience of electronic document management development in China. As the object of the study the main points and drawbacks of the use of electronic document management, government organizations and departments of enterprises are considered. The concept of electronic document management is the general notion of its process of movement. From creation to destruction or entry into the archive, as electronic documents are produced in large numbers and are gradually replacing paper documents as the main form of documents in modern society, electronic document management has also become a social problem that governments, organizations and individuals must address together. The practical significance of this work is that by analyzing and comparing different concepts and methods of electronic document management in other countries, serves as a guide for the development of similar areas in our country. The aim of the given work is to study the experience of the neighboring countries in the field of electronic document management in the context of our country to become the reference point for specialists in the field of electronic document management in two countries and to contribute to further development and realization of electronic document management. Based on this article, it was concluded that at present, electronic document management in China is gradually moving from «double track system» to «single track system». single track system», and this management mode will eventually replace the traditional electronic document management mode in the near future, which is not only a vane of industry development, but also the inevitable way forward for the information society.